RELEVANSI KURIKULUM SMK KOMPETENSI KEAHLIAN TEKNIK KOMPUTER DAN JARINGAN DENGAN TUNTUTAN SKKNI : Studi Evaluatif pada Kurikulum TKJ - Khairul Alfahani, - (2019)
The high unemployment rate of graduates of Vocational High Schools compared to graduates of other levels of education is the background for doing this research. With the rapid development of technology, almost all offices, government agencies, educational institutions and up to the level of housing have used information technology, especially computers as daily necessities. Therefore, researchers are interested in seeing and knowing how the relevance of the computer and network engineering skills competency curriculum that has the most closely related to computers and networks with Indonesian National Work Competency Standards demands. The focus of this research is on four aspects of the curriculum component contained in the vocational curriculum document. The general problem formulation in this study is the extent to which the relevance of the computer and network engineering competency curriculum with Indonesian National Work Competency Standards demands? there are four specific problem formulations in this study, namely; 1) what is the relevance of the objective formula in the computer and network engineering competency curriculum with Indonesian National Work Competency Standards demands? 2) what is the relevance of content in the computer and network engineering competency curriculum with Indonesian National Work Competency Standards demands? 3) how is the relevance of the learning process in the computer and network engineering competency curriculum with Indonesian National Work Competency Standards demands? 4) how is the relevance of learning evaluation in the computer and network engineering competency curriculum with Indonesian National Work Competency Standards demands? The research method used is descriptive evaluative with qualitative and quantitative approaches. Data collection techniques consist of documentation studies, interviews, observations and questionnaires. The results of the study indicate that the computer and network engineering competency curriculum is not fully relevant to the SKKNI demands. Thus, the school needs to evaluate and refine the curriculum, so that the creation of links and matches between the competencies possessed by students and the needs of employment. Keywords : Curriculum Relevance, Computer and Network Engineering Competency Curriculum, Indonesian National Work Competency Standards